Pyrite-Based Cr(VI) Reduction Driven by Chemoautotrophic Acidophilic Bacteria - Liu, Xinxing; Wu, Haiyan; Gan, Min; Qiu, Guanzhou (Frontiers in Microbiology, 2020)
Cr(VI) is considered as the priority pollutant and its remediation has attracted increasing attention in environmental area. In this study, pyrite-based Cr(VI) reduction driving by Acidithiobacillus ferrooxidans was systematically investigated. Results showed that pyrite based Cr(VI) reduction was a highly proton depended process, and pH influenced the biological activity. Passivation effect became more significant with pH increasing, along with the decrease of Cr(VI) reduction efficiency. However, Cr(VI) reduction efficiency enhanced with the inoculation of A. ferrooxidans. The highest reduction efficiency was achieved in the biological system with the pH range of 1-1.5. Pyrite dissolution and reactive sites regeneration was promoted by A. ferrooxidans, which resulted in the enhanced effect in Cr(VI) reduction. The low linear relevancy between pH and Cr(VI) dosage in the biological system indicated the complex interaction between bacteria and pyrite. Secondary iron mineral formation in pH unfavorable environment inhibited the pyrite dissolution. Yet the passivation effect relieved under the activity of A. ferrooxidans due to the S/Fe oxidization. The Balance between Cr(VI) reduction and biological activity was critical for sustainable Cr(VI) reduction. Pyrite based Cr(VI) remediation driven by chemoautotrophic acidophilic bacteria was an economical and efficient way for Cr(VI) reduction.